Modulatory Effects of Chinese Herbal Medicines on Energy Metabolism in Ischemic Heart Diseases - Fanghe Li; Jinmao Li; Saisai Li; Shuwen Guo; Ping Li (Frontiers Media S.A., 2020)
Ischemic heart disease (IHD), a major global public health problem, is associated with high morbidity and mortality. Although the very best of modern approaches have proven effective in reducing morbidity and mortality, the poor prognosis of patients with IHD remains a major clinical concern. Cardiac energy metabolism is increasingly recognized as having a role in the pathogenesis of IHD, inducing metabolic substrate alterations, mitochondrial dysfunction, impaired function of the mitochondrial electron transport chain, and deprivation of cardiac energy. Factors involved in cardiac energy metabolism provide potential therapeutic targets for the treatment of IHD. Chinese herbal medicines (CHMs) have a long history of use in the prevention and treatment of cardiovascular diseases with multi-component, multi-target, and multi-signaling. Increasing evidence suggests that Chinese herbal medicines may improve myocardial ischemia through modulating cardiac energy metabolism. Here, we describe the possible targets and pathways of cardiac energy metabolism for CHMs, and appraise the modulatory effects of CHMs on energy metabolism in IHD. Especially, this review focuses on summarizing the metabolic effects and the underlying mechanisms of Chinese herbal medicines (including herbs, major bioactive components, and formulas) in IHD. In addition, we also discuss the current limitations and the major challenges for research investigating the use of CHMs in the treatment of cardiovascular diseases.